An Assessment of ICT Infrastructure, Deployment and Applications in the Science and Technology (S&T) Research Institutions in Ghana - Kwafoa, Paulina Nana Yaa; Enstuah-Mensah, Clement (International Journal of Knowledge Content Development & Technology, 2021)
Abstract The paper discusses the Information Communication Technology (ICT) infrastructure as far as the availability of computers, local or wide area networks, Internet connectivity and its reliability, size of bandwidth and its optimization, etc. in the Science and Technology (S&T) research institution. It also examined the profile of the research scientists and looked at the type of ICT infrastructure that are available for their use as well as the reliability of the Internet connectivity within these research institutions. It looked at the broadband capacities of the research institutions and the ICT capabilities in respect of the technical and managerial support back-up that are available to the research institutions. The study used the survey research method with a questionnaire as well as personal observation to gather the data. From the data gathered, it was realized that the internet connectivity and the size of the bandwidth that the Research and Development (R&D) institutions subscribed to differed significantly. Again, the extent to which the research scientists were able to access the internet in their respective institutions depended on the quality of the local network in place. Generally, the investments in ICT were made for different management objectives, and these were meant to facilitate the generation of new knowledge as well as make measurable improvements in R&D activities. URL: http://ijkcdt.net/xml/28318/28318.pdf